Information Technology and Financial Services Competition - Hauswald, Robert; Marquez, Robert (Review of Financial Studies, 2003)
We analyze how two dimensions of technological progress affect competition in financial services. While better technology may result in improved information processing, it might also lead to low-cost or even free access to information through, for example, informational spillovers. In the context of credit screening, we show that better access to information decreases interest rates and the returns from screening. However, an improved ability to process information increases interest rates and bank profits. Hence predictions regarding financial claims' pricing hinge on the overall effect ascribed to technological progress. Our results generalize to other financial markets where informational asymmetries drive profitability, such as insurance and securities markets.